2022
DOI: 10.1001/jamanetworkopen.2022.3821
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Medication for Opioid Use Disorder Among US Adolescents and Adults With Need for Opioid Treatment, 2019

Abstract: This cross-sectional study of respondents to the National Survey on Drug Use and Health evaluates rates of medication for opioid use disorder receipt among people with need for treatment as well as associated sociodemographic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
79
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 69 publications
1
79
1
Order By: Relevance
“…Despite robust scientific evidence supporting the efficaciousness of MOUD, large treatment gaps persist. A recent study examining 2019 National Survey on Drug Use and Health (NSDUH) data on 2.2 million people meeting OUD criteria reported that only 27.8% had received MOUD during the prior year (Mauro et al, 2022). Those receiving MOUD were more likely to be adults with some college education and people living in large metropolitan areas (Mauro et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite robust scientific evidence supporting the efficaciousness of MOUD, large treatment gaps persist. A recent study examining 2019 National Survey on Drug Use and Health (NSDUH) data on 2.2 million people meeting OUD criteria reported that only 27.8% had received MOUD during the prior year (Mauro et al, 2022). Those receiving MOUD were more likely to be adults with some college education and people living in large metropolitan areas (Mauro et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examining 2019 National Survey on Drug Use and Health (NSDUH) data on 2.2 million people meeting OUD criteria reported that only 27.8% had received MOUD during the prior year (Mauro et al, 2022). Those receiving MOUD were more likely to be adults with some college education and people living in large metropolitan areas (Mauro et al, 2022). Among individuals receiving treatment for OUD, fewer than 35% receive MOUD, with the majority discontinuing during the first weeks or months (Williams et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, we know the vast majority of people with OUD still do not access treatment [ 1 ]. According to 2019 estimates, less than 30% of individuals needing OUD treatment received MOUD [ 14 ]. Of those who do enter care, few remain engaged with MOUD long enough to achieve lasting recovery [ 15 ]; treatment rates are lower for women versus men [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the epidemic has evolved from predominantly prescription opioid‐related deaths to those involving illicit and synthetic opioids. Recognizing the enduring need to learn from earlier waves and transitions, comprehensive assessments of patients' substance use [18] alongside expanded access and delivery of opioid use disorder treatment [19] could have greater impact on currently elevated risks in an increasingly deadly drug environment.…”
mentioning
confidence: 99%